miR-200b, ZEB2 and PTPN13 Are Downregulated in Colorectal Carcinoma with Serosal Invasion - Branislava Ranković; Emanuela Boštjančič; Nina Zidar; Margareta Žlajpah; Jera Jeruc (Biomedicines, 2022)
Serosal invasion is an independent negative prognostic factor in certain cancers, including CRC. However, the mechanisms behind serosal invasion are poorly understood. We therefore assumed that epithelial-mesenchymal transition (EMT) might be involved. Our study included 34 patients with CRC, 3 stage pT2, 14 stage pT3 and 17 showing serosal invasion (stage pT4a according to TNM staging system). RNA isolated from formalin-fixed paraffin-embedded tissue samples was analysed for expression of the miR-200 family and their target genes CDKN1B, ONECUT2, PTPN13, RND3, SOX2, TGFB2 and ZEB2 using real-time PCR. We found upregulation of miR-200b and ONECUT2 in CRC pT3 and pT4a compared to normal mucosa, and downregulation of CDKN1B in CRC pT3. Moreover, we observed, downregulation of miR-200b, PTPN13 and ZEB2 in CRC with serosal invasion (pT4a) compared to pT3. Our results suggest the involvement of partial EMT in serosal invasion of CRC. In addition, PTPN13 seems to be one of the important regulators involved in serosal invasion, and ONECUT2 in tumour growth.